2022
DOI: 10.1002/smll.202201989
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of 2D MXenes Based Zn‐Ion Batteries: Recent Development and Prospects

Abstract: Rechargeable zinc‐ion batteries (ZIBs) with exceptional theoretical capacity have garnered significant interest in large‐scale electrochemical energy storage devices due to their low cost, abundant material, inherent safety, high specific energy, and ecofriendly nature. Metal carbides/nitrides, known as MXenes, have emerged as a large family of 2D transition metal carbides or carbonitrides with excellent properties, e.g., high electrical conductivity, large surface functional groups (e.g., F, O, and OH), lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 340 publications
(326 reference statements)
0
49
0
Order By: Relevance
“…log (i) = b log (v) + log (a) (7) where v denotes the sweep rate, i denotes the peak current density, and a and b denote arbitrary constants. A b-value = 0.5 implied that capacitance was regulated via ionic diffusion, whereas b-value = 1.0 showed that the capacitive mechanism dominated during Using a three-electrode configuration in 1 M ZnSO 4 , the electrochemical performance of pristine Ti 3 C 2 T x -MXene and N-Ti 3 C 2 T x -MXene were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…log (i) = b log (v) + log (a) (7) where v denotes the sweep rate, i denotes the peak current density, and a and b denote arbitrary constants. A b-value = 0.5 implied that capacitance was regulated via ionic diffusion, whereas b-value = 1.0 showed that the capacitive mechanism dominated during Using a three-electrode configuration in 1 M ZnSO 4 , the electrochemical performance of pristine Ti 3 C 2 T x -MXene and N-Ti 3 C 2 T x -MXene were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules 2022, 27 with high-performing energy conversion devices [5,6]. Particular consideration has been given to designing rechargeable batteries [7] and supercapacitors (SCs) [8]. SCs are simple and risk-free technologies, but their low energy density is a primary limitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction and design of 1D nanoarchitecture and the flexibility of binder-free electrode material have shown great interest for electrode fabrication. The practical capacitance and stability of the metal oxide greatly depend on the composition, synthesis condition, and morphology of the structure [43,63,112,113,114,115,116,117]. Manikandan et al [118] designed binder-free vanadium oxide spider web-like nanostructure by using facile in situ hydrothermal technique for SSC devices.…”
Section: Spider Web-like Structurementioning
confidence: 99%
“…Strikingly, MXene not only possesses well-defined layered architectures, muscular mechanical rigidity, superior stability, the active metal centers, but also high surface area. Owing to the outstanding physicochemical characteristics, MXene has exhibited satisfactory performance in various researched fields over the past decade, including supercapacitors [ 39 , 40 ], catalysis [ 41 ], ion batteries [ [42] , [43] , [44] ], solar cells [ 45 ], water purification [ 46 ], electromagnetic interference shielding [ 47 ], sensors [ 48 , 49 ] and so on. The most remarkable thing is that, research evidences show that the MXene based interfacial heterostructure materials are ideal candidates to fabricate effective ECL biosensors in recent years.…”
Section: Introductionmentioning
confidence: 99%